Utilizing Oral Surveys to Better Understand Patient Satisfaction in a Low-Income, Urban Surgical Clinic. Issue 8 (August 2021) - Miller, Parker A.; Burgoon, Montgomry L.; Hoover-Hankerson, Bryson; Strand, Nicolle; Ross, Howard
Oral surveys allow patients to elaborate on their experience in the hospital, giving context to numerical values often used to assess patient satisfaction. This allows patients to speak about factors affecting satisfaction, which is important in complex, low-income populations. Spoken surveys were administered to 80 patients in surgery clinics at Temple University Hospital. Responses were transcribed and coded to analyze patient responses. Relationships among patient responses were identified, and responses were categorized to determine the most important factors related to patient satisfaction. Numerical data were also used to assess satisfaction. Patients were satisfied with their experience with the physician and the hospital, reporting averages scores of 9.73 and 9.19, respectively. Regarding physician satisfaction, patients cited effective communication and professionalism as being most important. As long as nothing went wrong, patients scored their experience outside their interactions with the physician highly. Negative experiences were mainly related to wait times and ineffective communication with office staff and were seldom related to the physician. By using a spoken survey, patients could elaborate on their responses which provides context to the numerical data. Despite the positive feedback for physicians, patients spoke openly about communication. In low-income populations, communication failures can be exacerbated by the power differential present between the patient and physician. Our study demonstrates the utility of oral surveys in understanding complex patient populations, and the results can be used to shape surgical and nonsurgical practices in similar patient populations.